Jamaica : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The Bank conducts Country Financial Accountability Assessments (CFAA) in all borrower countries. The specific objectives of the CFAA are to review the key aspects of public financial management at the national level: a) flow of funds to government entities and Bank projects, including planning, cash management, and budgeting; b) accounting and financial reporting; and c) auditing of public sector activities. The Bank carried out field work for a CFAA in Jamaica in May 2000. This CFAA makes the following recommendations: 1) Inefficient in the government's planning process and its subsequent integration into the budget process result in an inefficient execution of the budget, monitored mainly by cash flows rather than outputs. 2) Current budget formulation formats need to be simplified in order to increase their usefulness and assure more accurate estimates. 3) The government's decentralized cash management arrangements should be tightened to allow for greater central control over the amount of outstanding cash balances. 4) The government accounting function is more advanced than many Caribbean countries. However, there are still aspects to be improved. 5) The government's detailed financial reports on the budget and public sector expenditures should be more timely and focus more on actual expenditures rather than only the budgeted amounts. 6) As of 2000, the hardware and software of the Financial Management Information System (FMIS) needs to be upgraded.